Transformasi Pola Pikir Guru PAUD dalam Pendekatan Pembelajaran Deep Learning: Integrasi Growth mindset dan Fixed Mindset - Credo Gregori Betty; Engelbertus Nggalu Bali; Theodorina Novyani Seran; Sartika Kale; Angelikus Nama Koten (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
The implementation of deep learning approaches in Early Childhood Education (ECE) demands comprehensive readiness, particularly regarding teachers’ mindsets. However, limited research has examined how growth and Fixed mindsets influence pedagogical transformation in marginal areas such as Indonesia’s 3T regions (frontier, outermost, underdeveloped). This study aims to explore how teachers’ mindsets shape their responses to pedagogical innovation and how reflective thinking on mindset enhances meaningful and contextual learning. This study employed a descriptive qualitative approach through in-depth interviews and focus group discussions with 12 participants (teachers, headteachers, and school supervisors) across 13 districts in the 3T regions of East Nusa Tenggara. Data were analysed thematically using an inductive approach based on mindset framework. This study is limited by its geographical scope and small sample size. However, the findings hold significant implications for teacher training policies and the development of reflective learning communities in marginal contexts. Growth mindset  emerged as a crucial psychosocial asset enabling contextual teaching practices, whereas Fixed mindset was identified both as a barrier and as an adaptive response to systemic limitations. This study highlights teacher mindset as a systemic issue in 3T contexts and offers new contributions to the implementation of deep learning Iapproaches in early childhood education